Transform this equatio

  • Thread starter thomas49th
  • Start date
  • #1
thomas49th
655
0

Homework Statement



Need to rearrange this equation to make b subject
[tex]R = \frac{ab}{a+b}[/tex]



2. The attempt at a solution

R(a+b) = ab
Ra +Rb = ab
[tex]\frac{Rb}{b} = a [/tex] x -Ra


i think i did the last step wrong. Where do i go to now?

Thanks
 

Answers and Replies

  • #2
jing
123
0
after Ra + Rb = ab

using addition and subtraction you need to get all terms that have a factor b on one side of the equation and all terms that do not have a factor of b on the other side of the equation
 
  • #3
thomas49th
655
0
ive tried

[tex]\frac{Rb}{b} = a x -Ra[/tex]

but i think that's wrong

can you show me what you'd do here?
 
  • #4
jing
123
0
Yes it wrong. Go back to the step where you were correct (see my last post) and do not do any division at this stage. Have another read of my post and let me know if you do not understand what I am suggesting you do.
 
  • #5
thomas49th
655
0
Ok

Ra + Rb = ab

can be written as

Ra + Rb = a x b

dont you cancel out x b with a /b (divide b)

If not, and you just use +/- then isn't it

Ra + Rb = ab
Rb - b = a - Ra
b(R-1) = a - Ra
b = a - Ra/(R-1)
But that doesn't look right to me...
Thanks
 
  • #6
cristo
Staff Emeritus
Science Advisor
8,140
74
Ok

Ra + Rb = ab

can be written as

Ra + Rb = a x b

dont you cancel out x b with a /b (divide b)

If not, and you just use +/- then isn't it

Ra + Rb = ab
Rb - b = a - Ra
b(R-1) = a - Ra
b = a - Ra/(R-1)
But that doesn't look right to me...
Thanks

No, this is not right. You have: Ra+Rb=ab. Collect the terms including b together on one side: Ra=ab-Rb.

Now, can you factorise the right hand side? Once you have it factorised, it should be easy to make b the subject.
 
  • #7
jing
123
0
Ok

If not, and you just use +/- then isn't it

Ra + Rb = ab
Rb - b = a - Ra
b(R-1) = a - Ra
b = a - Ra/(R-1)
But that doesn't look right to me...
Thanks

No you cannot separate the ab except by division

Ra + Rb = ab subtract Rb from both sides
Ra = ab -Rb factorise
Ra = b(a - R) now do the division to obtain b
 
  • #8
thomas49th
655
0
Ra = ab - Rb
b(a-R) = Ra
b = Ra/(a - R)
 
  • #9
jing
123
0
Yes it is right
 

Suggested for: Transform this equatio

Replies
4
Views
242
  • Last Post
Replies
8
Views
187
Replies
3
Views
267
Replies
9
Views
146
  • Last Post
Replies
7
Views
681
Replies
1
Views
214
Replies
1
Views
224
Replies
1
Views
209
Replies
3
Views
240
Replies
31
Views
926
Top